OPTIMALISASI MANFAAT PETERNAKAN SAPI TERPADU PT KPC SEBAGAI PROGRAM PEMANFAATAN LAHAN BEKAS TAMBANG UNTUK KEMAJUAN PENDIDIKAN TINGGI DI KUTAI TIMUR - Joni Ariansyah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
In the framework of ex-mining land use and development of the company's CSR program, PT KPC East Kutai create integrated programs in the livestock sector called Integrated Breeding Beef Cattle Farm program (in Indonesian : Peternakan Sapi Terpadu aka PESAT) , which is the integration activities of Bali cattle breeding, dairy and dairy products until the product is finally at the top ex mining land . This program has been started since the end of 2009. MoU between PT KPC and STIPER of East Kutai has a special meaning, especially for farm studies program. This program can be used as a field laboratory for STIPER campus, which does not have such facilities. Accordingly, necessary to study the extent to which the program contributes for advancement of higher education in East Kutai. This study aims to 1) identify the benefits obtained by STIPER from the program , 2) estimate the benefits of the program for the campus STIPER and 3) evaluate the contribution program to the advancement of education on campus STIPER. This study uses qualitative and quantitative methods, that is by identifying what benefits resulting from the program and further quantify in the form of rupiah and evaluate it . The results showed that there are several benefits obtained from the program , as well as the street vendors and research into the field laboratory. If quantified, the benefits worth USD 28.9 million / year, with details of benefits as a field laboratory of Rp 10,500,000 / year and as a street vendor and research of Rp 3.4 million / year. The conclusion of this study that PESAT program not yet optimalized with good.